Alternative Strategies with Iodine: Fast Access to Previously Inaccessible Iodine(III) Compounds. Issue 27 (6th June 2018) - Hokamp, Tobias; Mollari, Leonardo; Wilkins, Lewis C.; Melen, Rebecca L.; Wirth, Thomas
Abstract: Non‐iodinated arenes can be easily and selectively converted into (diacetoxyiodo)arenes in a single step under mild conditions by using iodine triacetates as reagents. The oxidative step is decoupled from the synthesis of hypervalent iodine(III) reagents, which can now be prepared conveniently in a one‐pot synthesis for subsequent reactions without prior purification. The chemistry of iodine triacetates was also expanded to heteroatom ligand exchanges to form novel inorganic hypervalent iodine compounds. Abstract : A fast and efficient access to previously inaccessible iodine(III) reagents has been developed. The method has proved useful in synthesis since the oxidation step is decoupled from the iodination step.